Morphological characterization of the leukocytes in circulating blood of the turtle (Phrynops hilarii) - Pitol, Dimitrius Leonardo [UNESP]; Issa, João Paulo Mardegan; Caetano, Flávio Henrique [UNESP]; Lunardi, Laurelúcia Orive (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2007)
The Phrynops hilarii specie of turtle has its characterization not well defined in the literature, it was proposed in this study the leukocyte characterization of the blood, stained by Leishman and analyzed under light and transmission electron microscope. It was not observe any cellular type with similar characteristics to neutrophils in mammalian group. We believed, based on the data obtained in this study that the heterophils have a morphofuncional analogy with another neutrophils belonged to mammalian group. This conclusion is being supported in many recent studies found in the literature.
Keywords: Blood; Leukocytes; Morphology; Turtle